Vibrations measurement of the funicular generated vibrations on Gediminas Hill North part slope - Skuodis, Šarūnas; Kelevišius, Kęstutis; Žaržojus, Gintaras (International Conference “Environmental Engineering”, 2017)
An experimental measurements of the funicular generated vibrations provided after Gediminas Hill North part slope landslide, which occurred on 2016. The geology of Gediminas Hill made up strata of Quaternary system late Pleistocene glacial and glaciofliuvial coarse and fine deposit. The purpose of this measurement was to determine, whether funicular generated vibrations during exploitation is the significant slope destabilizing factor. For vibration measurements in X, Y and Z directions were implemented equipment, developed by the authors. Measurements in 25 different points on the Gediminas Hill slope were perfirmed during funicular movement up and down. Analysis of obtained results revealed, that the highest vibration level mainly localized at the top of funicular foundations, wave energy is not large, propagating waves greatly dampens in the soil and there is no effect for general slope stability and the funicular exploitation was not the main reason of the occurred landslide in 2016 Spring.
Keywords: vibrations monitoring; slope landslide; vibrations measurement; ground vibrations